2023
DOI: 10.1186/s12884-023-05379-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Norwegian pregnant women and men with pregnant partners, and association with perception of sleep and depressive symptoms: a cross-sectional study

Abstract: Background Pregnant women and men with pregnant partners experience variations in quality of life (QoL) during pregnancy, a period characterized by physical, psychological, and social changes. Pregnancy is associated with reduced QoL, depressive symptoms, and sleep problems. This study aimed to: (1) determine whether Norwegian pregnant women and men with pregnant partners differed in QoL levels in the third trimester of pregnancy; (2) determine whether the relationship between perception of sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Similarly, a study conducted in Norway, between October 2018 and December 2019, involving pregnant women in the third trimester of pregnancy, showed that the highest quality of life score was observed in the psychological and environmental domains. 4 However, a study carried out with women in the third trimester of pregnancy, receiving care in PHC in Rio Branco, the capital city of the state of Acre, from March to May 2011, showed a lower average for the environmental domain (60.8 ± 9.4). The highest averages were found in the physical (75 ± 11.6), psychological (73.3 ± 10.6) and social relationship (74 ± 12.4) domains.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, a study conducted in Norway, between October 2018 and December 2019, involving pregnant women in the third trimester of pregnancy, showed that the highest quality of life score was observed in the psychological and environmental domains. 4 However, a study carried out with women in the third trimester of pregnancy, receiving care in PHC in Rio Branco, the capital city of the state of Acre, from March to May 2011, showed a lower average for the environmental domain (60.8 ± 9.4). The highest averages were found in the physical (75 ± 11.6), psychological (73.3 ± 10.6) and social relationship (74 ± 12.4) domains.…”
Section: Discussionmentioning
confidence: 98%
“…The theoretical basis was based on bibliographic studies in the scientific literature to evaluate the relationship between violence and quality of life with covariates ( Figure 1 ). 1 , 2 , 4 , 5 , 10 - 12 The minimum adjustment sets provided by the DAGitty program included the following variables: age, race/skin color, marital status, schooling, monthly income, parity, and pregnancy planning. 13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention group consisted of first-time mothers and their partners from three different city districts participating in the regular CHS programme and the NF home visiting programme. Despite efforts to recruit a diversity of participants to the larger research project, most participants were partnered, had a high educational level and were ethnic Norwegians ( Brekke et al, 2023 ). Inclusion criteria in the present study were couples in the intervention group who had answered the final questionnaire in the research project 12 months postnatally – between March and June 2020 – and who had consented to be contacted for further research.…”
Section: Methodsmentioning
confidence: 99%